The Influence of Team Quiz Learning Method on the Ability to Determine Intrinsic Elements of Fantasy Stories in Grade VII Junior High School Students - Nurazizah, Nurazizah; Kusyani, Diah; Wulandari, Wina (Lembaga Riset Mutiara Akbar, 2025)
Indonesian language learning on fantasy story material at SMP Al-Washliyah 8 Medan still uses conventional lecture methods that are less interesting for students. This study aims to test the effect of the team quiz method on students' ability to determine the intrinsic elements of fantasy stories. This study is a quantitative experiment with a nonequivalent control group pretest-post test design. The sample consisted of 60 students divided into experimental and control classes. Data was collected through tests, observations, and documentation. The results showed that after the application of the team quiz method, the average posttest score of the experimental class increased to 81.5 compared to the control class which only reached 75.8. The t-test analysis showed that tcount> ttable (2.660> 1.701), so it can be concluded that the team quiz method has a significant effect on improving students' ability to determine the intrinsic elements of fantasy stories.